Direct identification of trypanosomatids by matrix‐assisted laser desorption ionization–time of flight mass spectrometry (DIT MALDI‐TOF MS). (29th June 2016) - Avila, C. C.; Almeida, F. G.; Palmisano, G.
Abstract : Accurate and rapid determination of trypanosomatids is essential in epidemiological surveillance and therapeutic studies. Matrix‐assisted laser desorption ionization/time of flight mass spectrometry (MALDI‐TOF MS) has been shown to be a useful and powerful technique to identify bacteria, fungi, metazoa and human intact cells with applications in clinical settings. Here, we developed and optimized a MALDI‐TOF MS method to profile trypanosomatids. trypanosomatid cells were deposited on a MALDI target plate followed by addition of matrix solution. The plate was then subjected to MALDI‐TOF MS measurement to create reference mass spectra library and unknown samples were identified by pattern matching using the BioTyper software tool. Several m / z peaks reproducibly and uniquely identified trypanosomatids species showing the potentials of direct identification of trypanosomatids by MALDI‐TOF MS. Moreover, this method discriminated different life stages of Trypanosoma cruzi, epimastigote and bloodstream trypomastigote and Trypanosoma brucei, procyclic and bloodstream. T . cruzi Discrete Typing Units (DTUs) were also discriminated in three clades. However, it was not possible to achieve enough resolution and software‐assisted identification at the strain level. Overall, this study shows the importance of MALDI‐TOF MS for the direct identification of trypanosomatids and opens new avenues for mass spectrometry‐based detection of parasites in biofluids. Copyright © 2016 John Wiley & Sons, Ltd.